Post-closure career paths of self-employed workers - MinSub Kim (KDI Journal of Economic Policy, 2024)
This study documents self-employed workers' characteristics associated with their career paths after a business closure in order to improve employment insurance for such workers. Utilizing work history data from the Korean Labor & Income Panel Survey, a competing-risks regression model is adopted in order to study how self-employed workers' career paths after unemployment (i.e., business closure) vary according to their characteristics. The findings suggest that the post-closure career paths of self-employed workers are associated with (i) their revenue and income, (ii) the individuals' demographic characteristics, and (iii) the industry in which they operate. Several policy implications for employment insurance that better caters to the needs of self-employed workers are derived from the empirical results.
Keywords: J64; J65; J68; 330; Self-Employment; Unemployment; Employment Insurance; Career Path